PROSECUTORIAL SUPERVISION TOWARDS THE RECEIPT, REGISTRATION AND VERIFICATION OF CRIME REPORTS : Prosecutorial supervision towards the receipt, registration and verification of crime reports - Ghazaryan, Tigraniravaban (State and Law, 2020)
As a result of receiving, registering, inspecting, and preparing materials forcriminal reports, the law enforcement agencies allow numerous abuses in practice thatdirectly lead to from on one hand to the violation of the legal interests of the peoplewho presented reports. Alleged victims and on the other hand, to the violation of therights and legitimate interests of the person who has allegedly committed a crime.Therefore, in order to ensure legality at the stage of initiating criminal proceedings, thelegislature has made the activities of the mentioned bodies designated subject toprosecutorial control and judicial supervision, also emphasizing the role andimportance of the stage of initiating criminal proceedings.The fixation of the proper mechanisms aims to not only detect and eliminate thelegal infringements, but also to prevent them, having as their object the discovery,elimination, prosecution or discovery of groundless denial of initiating a criminalproceeding at the stage of criminal proceedings.
Keywords: to initiate criminal proceeding, a person who has allegedly committed a crime, to initiate a criminal case, prosecutorial supervision, acceptance of reports, registration, inspecting, judicial supervision